2008
DOI: 10.1080/10520290701822436
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical detection of EGFR, p185erbB-2, Bcl-2 and p53 in breast carcinomas in pre-menopausal and post-menopausal women

Abstract: Young pre-menopausal women with breast carcinomas have an overall worse prognosis than older, post-menopausal women. Because histologic grade is a major predictor of tumor behavior and correlates with biomarker expression, we assessed the immunohistochemical expression of epidermal growth factor receptor (EGFR), p185(erbB-2) and Bcl-2, and nuclear accumulation of p53 in breast carcinomas in pre- and post-menopausal women with equivalent histologic grades. This allowed identification of differences in biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…It has been reported in some investigations that EGFR expression could be significantly associated with nuclear grade [14,15]. In the current study, the proportion of nuclear grade 3 tumors was found to be comparatively higher in EGFR-expressing cancers.…”
Section: Discussionsupporting
confidence: 57%
“…It has been reported in some investigations that EGFR expression could be significantly associated with nuclear grade [14,15]. In the current study, the proportion of nuclear grade 3 tumors was found to be comparatively higher in EGFR-expressing cancers.…”
Section: Discussionsupporting
confidence: 57%
“…The breast cancers constituting the microarrays were also immunostained for detection of expression of ER, PR, ErbB2, p53, Bcl2, p27 Kip1 and Ki-67, as previously described [31, 32]. Each of these protein biomarkers functions in the growth and progression of breast cancer and is a prognostic indicator or is associated with other indicators of prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…Expression of ErbB2 at the cell membrane and cytoplasmic expression of Bcl2 were semiquantified by the same immunoscoring system used for BRMS1 and as previously described [31]. For ER, PR, p53, Ki-67 and p27 Kip1 , the percentage of cells with nuclear staining was determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formalin-fixed, paraffin-embedded primary breast cancer tissues with corresponding non-cancerous, histologically normal breast tissue from the cancer resection specimens were obtained from the archives of the UAB Department of Pathology after Institutional Review Board approval. The breast cancer tissues were characterized for estrogen receptor (ER), progesterone receptor (PR), and Her2/neu expression by IHC, as described previously (Talley et al 2002(Talley et al ,2008.…”
Section: Cell Lines and Breast Tissuesmentioning
confidence: 99%